Impact of population mobility on regional carbon emissions: empirical evidence from Australia - Guo, Hongbo (Frontiers in Environmental Science, 2024)
Understanding carbon emissions through the lens of population mobility is crucial for addressing sustainability challenges and fostering economic development. This study aims to investigate the influence of population mobility on carbon emissions in Australia, providing insights for targeted policy interventions. Utilizing panel datasets spanning from 2007 to 2020, encompassing both international and domestic migration in Australia, empirical analyses were conducted. The focus was on assessing the relationship between population mobility and regional carbon emissions. The study reveals distinct effects of domestic and international population mobility on carbon emissions. Domestic mobility demonstrates a negative correlation, whereas international mobility shows a positive association with carbon emissions. Moreover, significant regional heterogeneity in carbon emissions is observed, influenced by economic development and population size variations between eastern and western regions. These findings underscore the importance of tailored emission reduction strategies based on the nature of population mobility. By elucidating the intricate dynamics between mobility patterns and carbon emissions, this study contributes to a nuanced understanding of CO2 emission trends, informing policy decisions amidst the challenges posed by global climate change.